The Effect of Accounting Understanding and Sak Etap Implementation on the Quality of MSME Financial Reports in Sidoarjo Regency: Pengaruh Pemahaman Akuntansi dan Implementasi Sak Etap Terhadap Kualitas Laporan Keuangan Umkm di Kabupaten Sidoarjo - Khasanah, Uswatun; Nurasik, Nurasik (Indonesian Journal of Innovation Studies, 2022)
The purpose of this study was to determine the effect of accounting understanding on the quality of financial statements and the effect of the implementation of SAK ETAP on the quality of financial statements. The approach used in this research is a quantitative approach. This research was carried out in all MSMEs that were sampled and who had domiciles in the Sidoarjo Regency area. Researchers will directly go to MSMEs that meet the criteria as samples in this study to distribute questionnaires and after a specified period of time, researchers will return and take questionnaires. The analysis technique uses multiple linear regression analysis and hypothesis testing. In collecting data using a questionnaire. Based on the results of the study, it was proven that accounting understanding had a positive effect on the quality of financial statements, tested using the t-test, the results of the tcount value of the accounting understanding variable (X1) were 4.854 with a significance value of 0.000 so (0.000 <0.05). Then the implementation of SAK ETAP has a positive effect on the quality of financial reports, it is known that the t-count value of the SAK ETAP implementation variable (X2) is 15.678 with a significance value of 0.000 so (0.000 <0.05).